2021
DOI: 10.22541/au.162401408.86380475/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of African swine fever virus (ASFV) infection in domestic pigs infected with virulent, moderate virulent and attenuated genotype II ASFV European isolates.

Abstract: This study aimed to compare the infection dynamics of three genotype II African swine fever viruses (ASFV) circulating in Europe. Eighteen domestic pigs divided into three groups were infected intramuscularly or by direct contact with two haemadsorbent ASFVs (HAD) from Poland (Pol16/DP/ OUT21) and Estonia (Est16/WB/Viru8), and with the Latvian non-HAD ASFV (Lv17/WB/Rie1). Parameters such as symptoms, pathogenicity, and distribution of the virus in tissues, humoral immune response, and dissemination of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The average time of ASF symptom onset after exposure to ASFV was about 5 to 13 days and death of the infected pigs began to occur at 8-15 days after exposure (11,22). The time period from the onset of the disease to death of the animal is relatively short and the morbidity and mortality rate is almost 100% (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average time of ASF symptom onset after exposure to ASFV was about 5 to 13 days and death of the infected pigs began to occur at 8-15 days after exposure (11,22). The time period from the onset of the disease to death of the animal is relatively short and the morbidity and mortality rate is almost 100% (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Eight serotypes are also known based on viral hemagglutinin CD2-like protein (CD2v) and C-type lectin (2,5,6). Among these, genotype II stain is highly virulent and is prevalent in Europe, Russia, China, and Southeast Asia (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn usually leads to low mortality on farms in the early phase, usually within 2 to 3 weeks after virus introduction, though after this period most of the animals in the same pen will be infected. To date, all ASF viruses detected in domestic pigs and the majority of wild boar in Latvia were virulent strains despite the finding of an attenuated strain in a hunted wild boar in 2017 (Gallardo, Soler, et al., 2019; Gallardo et al., 2021). Taking into account that the dominant ASFV genotype II strains currently circulating are causing a case‐fatality rate of >90%, seropositive healthy pigs are rarely found as majority of pigs do not survive the acute phase (Blome et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative data, such as symptoms, pathogenicity and virus distribution in tissue, have been presented for different strains of the ASFV genotype II currently circulating in Europe (Gallardo et al., 2021). That study aimed at expanding current knowledge of ASFV transmission through inoculation and direct transmission experiments using three different strains (from Estonia, Latvia and Poland).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the different strains had different virulence, with the Polish strain causing rapid and fatal disease. The Estonian variant caused subacute infections, whereas the Latvian variant induced milder clinical symptoms (Gallardo et al., 2021).…”
Section: Introductionmentioning
confidence: 99%